Verbal working memory in children with mild intellectual disabilities. - Van der Molen MJ; Van Luit JEH; Jongmans MJ; Van der Molen MW (Journal of Intellectual Disability Research, 2007)
Background: Previous research into working memory of individuals with intellectual disabilities (ID) has established clear deficits. The current study examined working memory in children with mild ID (IQ 55-85) within the framework of the Baddeley model, fractionating working memory into a central executive and two slave systems, the phonological loop and visuo-spatial sketchpad. Method: Working memory was investigated in three groups: 50 children with mild ID (mean age 15 years 3 months), 25 chronological age-matched control children (mean age 15 years 3 months) and 25 mental age-matched control children (mean age 10 years 10 months). The groups were given multiple assessments of the phonological-loop and central-executive components. Results: The results showed that the children with mild ID had an intact automatic rehearsal, but performed poorly on phonological-loop capacity and central-executive tests when compared with children matched for chronological age, while there were only minimal differences relative to the performance of the children matched for mental age. Conclusions: This overall pattern of results is consistent with a developmental delay account of mild ID. The finding of a phonological-loop capacity deficit has important implications for the remedial training of children with mild ID.